ESTUDIO AL NIVEL DE IDEA PARA EL LANZAMIENTO DE UN SATÉLITE DE COMUNICACIONES PARA EL SERVICIO DEL ESTADO PERUANO - Hidalgo Sánchez, Augusto (2009)
The peruvian government is affordable and should launch a geosynchronous satellite (GEO) of 5 ton of usable load. It could cost around US$ 450 million, which includes manufacture, launching, setting in orbit, terrestrial equipment and operation from a station located in Peru. The life expectancy of the device could be in the range of 20 years. This satellite must be devoted to education, especially rural, to public health, the surveillance of the borders, the construction of a national defense communications system, the monitoring of the environment, the creation of a backbone for telephone business, the GPS service, the location of fish ships, as well as, the support of internet, among other services. However, the achieving of this goal faces several challenges, the first is the unavailability of an orbital position for this device. Up to now, there are around 850 GEO satellites, which belong to the developed countries, USA and Russia, and technically have filled up the orbits, since de 60´s. That problem, as well as, the problems of designing, construction, launching and operation of the satellite requires the participation of an strategic partner. This partner could be Russia, due its expertise in these business, the GEO orbits they currently manage, and due to the military links with Peru. In Latin America, only Cuba have stronger links to Russia. Nevertheless, another partner could be Brazil, however, Peru will have to wait some 5 years or so until Brazil completes its spatial capabilities.